Penatalaksaan Demam Tifoid Dan Pencegahan Holistik Pada Pasien Wanita Usia 61 Tahun Melalui Pendekatan Kedokteran Keluarga - Karine Meynda Putri; Sahab Sibuea (Medula, 2020)
Fever is an acute infectious disease caused by Salmonella typhi bacteria. Fever often occurs in several countries in the world and generally occurs in countries with low levels of cleanliness. Based on data from WHO (World Health Organization) estimates the incidence rate in the world around 17 million people per year, the death rate from typhoid fever reaches 600,000 and 70% occur in Asia. To identify risk factors and problems with patient management based on the patient's problem by seeking family approval. This study is a case report. Primary data were obtained through history taking, physical examination and home visits. Secondary data were obtained from the patient's medical record. Assessment is based on a preliminary, process, and final diagnosis of a qualitative and quantitative study. Patients have functional degrees 2 with typhoid fever which has internal risk factors, namely lack of knowledge related to typhoid fever and the process of infection of the surrounding environment. External risk factors are unclean home environment. Then educating patients and families about typhoid fever for a clean and healthy life. Clinical problems in patients need attention to changes in clean and healthy living behavior. Health workers support not only solving clinical problems, but also finding and providing solutions to problems in the environment that affect the health of patients and families